Bajo’s Living Law on Environmental Preservation to Support Economic Improvement - Amanda Adelina Harun (Dialogia Iuridica, 2023)
Bajo is a tribe that has a uniqueness, they settled in coastal or shallow water areas. The uniqueness of the settlements and the natural conditions of the Bajo people can be a tourism potential to improve the economic conditions of the Bajo people. Tourism requires preserved environmental conditions. The Bajo has a 'living law' related to the preservation of coastal and marine areas, such as the prohibition of throwing garbage and household waste into the sea, the prohibition of killing turtles, the prohibition of destroying corals, and the prohibition of going to sea during the spawning period of fish. Bajo's 'living law' is in the form of unwritten law, so it has several weaknesses. First, because the unwritten form is feared to shift and could be lost, second, the implementation could not be enforced by the official because it is not official law. A good official law is one that is in accordance with the 'living law', so it would be better to adopt the 'living law' of Bajo in the official law, for the sake of preserving the environment, and support economic improvement through tourism.